Trend of Implementation Foster Family Toddlers (FFT) Programin East Java Province at 2015-2019 (Medico Legal Update, 2021)
Foster Family Toddlers (FFT) as an effort program to improve the knowledge and skills of parents fosteringthe development of children in a whole and optimal way. The result of 2018 Basic Health Research, EastJava Province shows the percentage low birth weight is 6.5%, underweight of toddler is 15%, wasting oftoddler is 8% and the coverage of exclusive breast milk is 40%. East Java Health Profile 2018 showed of lowbirth weight is 3,7% and the coverage of exclusive breast is 76.83%, underweight and wasting in toddler isnot found numbers, but there is the weight of toddler in under red line is 0.77%. Therefore, needs to knowtrend of the implementation of FFT in East Java. This study was quantitative descriptive research designwith secondary data. The result showed the reporting of FFT group from 2015-2017 increased by 4.52% anddecreased in 2017-2019 by 4.52% and has not reached the target of KKP 80%. FFT member participationin 2015-2017 increased by 3.78% and decreased in 2017-2019 by 12.55%. FFT family attendance at the2015-2016 Meeting increased by 1.38% and decreased in 2016-2019 by 1.24%, and the family of membersof FFT Child Card Users in 2015-2019 saw a continuous increase of 9.52%. So the result of the trend of theimplementation of activities is less maximal because there are still some obstacles to be considered.